Public Ethics and the Legitimacy of Indonesian Democracy: Protests over DPR Allowances, Elite Conflict, and Civil Response: Etika Publik dan Legitimasi Demokrasi Indonesia: Protes Tunjangan DPR, Konflik Elite, dan Respons Sipil - M. Reza Saputra (Journal of State Democracy, 2025)
This study examines the August 2025 controversy over parliamentary allowances in Indonesia as a critical case of public ethics failure and its impact on democratic legitimacy. By applying a qualitative case‐study approach and critical discourse analysis of primary news sources and academic literature, the research investigates elite rhetoric and actions that revealed profound disconnects from citizen realities. It further explores how digitally mediated civil responses transformed latent frustration into coordinated mass protests, amplifying challenges to institutional trust. The analysis situates these events within structural weaknesses of Indonesia’s “fat coalition” system, demonstrating how the absence of effective legislative opposition fosters elite impunity and ethical erosion. Findings highlight the causal sequence from coalition dynamics to oversight failure, elite misconduct, civic mobilization, and legitimacy crisis. The study concludes that without fundamental reforms to strengthen checks and balances particularly a functional legislative opposition Indonesia’s democracy remains vulnerable to recurring cycles of elite impunity and public distrust.